Game Cross Efficiency Method for Assessing the Potential of Biomass Materials in Briquette Production - Kailomsom, Prasit; Chaiphet, Kumpanat (Journal of Engineering and Industrial Technology, Kalasin University, 2023)
The concept of processing biomass materials into charcoal briquettes is one way to address the energy shortage issue in the country. It's also a promising idea for utilizing agricultural waste effectively. However, assessing the potential of biomass materials for conversion into fuel is complex due to several critical properties that need consideration. Therefore, this research proposes a stepwise efficiency evaluation method. The initial step involves defining the key properties for the fuel potential, such as moisture content, ash content, volatile matter, fixed carbon, and calorific value. Next, a game-cross-efficiency approach is employed to measure the potential of various biomass materials with multiple properties. The method was tested on 23 different biomass types, revealing that rubberwood, corn cob, and bamboo are the top three suitable materials for processing into the charcoal briquettes in descending order. Additionally, the proposed method was compared with well-known techniques in the literature, showing a very high correlation (Spearman rank correlation coefficient). This suggests that the proposed method is reliable and can be applied for assessing the fuel potential of different biomass materials.